2009
DOI: 10.1371/journal.pone.0008135
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Factors and Non-Hodgkin Lymphoma Risk in the California Teachers Study

Abstract: BackgroundNon-Hodgkin lymphoma (NHL) is a malignancy etiologically linked to immunomodulatory exposures and disorders. Endogenous female sex hormones may modify immune function and influence NHL risk. Few studies have examined associations between reproductive factors, which can serve as surrogates for such hormonal exposures, and NHL risk by subtype.Methodology/Principal FindingsWomen in the California Teachers Study cohort provided detailed data in 1995–1996 on reproductive history. Follow-up through 2007 id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
42
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 29 publications
8
42
1
Order By: Relevance
“…One recent study found a positive association between reproductive factors and the risk of NHL, but others reported no association [43][44][45]. Although these proposed factors were not validated in our study, we found a difference in age at menarche between cases and controls, albeit without statistical significance.…”
Section: Discussioncontrasting
confidence: 89%
“…One recent study found a positive association between reproductive factors and the risk of NHL, but others reported no association [43][44][45]. Although these proposed factors were not validated in our study, we found a difference in age at menarche between cases and controls, albeit without statistical significance.…”
Section: Discussioncontrasting
confidence: 89%
“…With a 30% lower incidence rate for women, male gender per se may be considered a risk factor [5,27]. It has been postulated that this is mostly based on the influence of sex hormones (and particularly estrogen) on the immune system [27,28]. Consequently, also pregnancy and live births were shown to be protective factors with a risk reduction of 0.84 (95% CI 0.68-1.04) [28].…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that this is mostly based on the influence of sex hormones (and particularly estrogen) on the immune system [27,28]. Consequently, also pregnancy and live births were shown to be protective factors with a risk reduction of 0.84 (95% CI 0.68-1.04) [28]. Interestingly, and in line with the fact that clinical behavior and prognosis significantly differ between lymphoma subsets, SEER data have demonstrated that though men are more likely to suffer from NHL in general, some entities are evenly distributed or even more likely to arise in women including follicular lymphoma and marginal zone lymphoma [5].…”
Section: Discussionmentioning
confidence: 99%
“…For most of these factors, associations have been observed in both directions, and significantly increased or decreased risks of NHL from one study were not replicated by others. 15,[17][18][19][31][32][33] The only exception is an inverse association between parity and NHL, which was reported by more than two studies. 23 As far as the associations with menopausal hormone use in observational studies are concerned, case-control studies have generally reported decreased risks of NHL among menopausal hormone users, yielding a pooled odd ratio (OR) of 0.70 (95% CI 0.54-0.90) in an international pooled analysis, InterLymph.…”
Section: Discussionmentioning
confidence: 99%